In Memoriam Professor Andrzej RAKOWSKI - Andrzej MIŚKIEWICZ (Archives of Acoustics, 2018)
prof. dr hab. Andrzej Rakowski, creator of the psychoacoustics school well-known in Poland and around the world, long-time Scientific Secretary, Chairman and Honorary Chairman of the Polish Academy of Sciences, Member and Founder of the Polish Acoustic Society, member of many global acoustic organizations, outstanding scientist and recognized world scientific authority acoustics, irreplaceable master and friend of many generations of acoustics, a man of great heart and mind.